Transnational Migration and Reconfiguration of the Family in Zimbabwe - Jaji, Rose (2022)
The unprecedented transnational migration ensuing from the economic crisis in Zimbabwe has sociocultural impacts on both the migrants and non-migrant family members. This article, which draws from qualitative research with migrants and non-migrants, discusses how migration upsets cultural configurations of the family in terms of marriage, parenthood, childhood, the gender and age division of labor and family relations. The transformation of family life which transnational migration engenders is observable at both nuclear and extended family levels where it has destabilized traditional family structures by creating relations and gender roles that challenge cultural and social values relating to the family. Transnational migration has also transformed the family’s place in the migrant’s life and vice versa in ways that deviate from the cultural norm.